Masquerading as an Orbital Malignancy: A Rare Presentation of Pott’s Puffy Tumor with Intraorbital Extension in a Diabetic Adult - Suhery; Mardijas Efendi; Silvia Roza; Hesty Lidya Ningsih (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Pott’s puffy tumor (PPT) is a rare, life-threatening clinical entity characterized by frontal bone osteomyelitis and subperiosteal abscess, typically resulting from untreated frontal sinusitis. While predominantly a pediatric diagnosis, adult presentation is exceptionally rare and often associated with immunocompromised states. The clinical mimicry of PPT, particularly when presenting with bone destruction and orbital extension, frequently leads to misdiagnosis as a malignant neoplasm. This study aims to report a rare and instructive case of Pott’s puffy tumor in a 52-year-old diabetic female. Case presentation: We report a case of a 52-year-old female with uncontrolled Type 2 Diabetes Mellitus presenting with progressive left ocular proptosis, globe displacement, and blurred vision persisting for two months. Imaging revealed a heterogeneous mass in the frontoethmoidal sinus with extensive osteolytic destruction of the orbital roof and frontal bone, initially raising strong suspicion of a sinonasal malignancy or metastasis. The patient underwent a bicoronal craniectomy and debridement. Intraoperative findings revealed a purulent subperiosteal collection and necrotic bone, confirming the diagnosis of PPT with intraorbital extension. The defect was repaired via craniofacial reconstruction using bone cement. Post-operative culture analysis confirmed a polymicrobial infection. Conclusion: This case underscores the necessity of maintaining a high index of suspicion for PPT in diabetic adults presenting with proptosis and osteolytic radiographic findings. Although rare, PPT can masquerade as a malignancy. Early recognition and a multidisciplinary approach combining aggressive surgical debridement with targeted antibiotic therapy are imperative to prevent catastrophic intracranial and orbital complications.